Political parties in troubled times: economic crisis and voter's perceptual bias of parties' ideology in Europe - Belchior, A. M. (2022)
To what extent did the 2010 economic crisis in Europe accentuate voters’ perceptual bias of parties’ ideological positions? This article investigates the perceptions of voters concerning the left-right positioning of parties by testing the displacement theory effects. Two moments in time are considered: before and after the economic crisis emerged (2009 and 2014), covering a sample of seven European countries (countries most and least affected by the crisis). It is argued displacement effects have increased after the emergence of the crisis, especially right-wing contrast effects in those countries most affected. Analysis using micro-level data from the European Election Studies (2009-2014) and party-level data from the Chapel Hill experts’ survey (2006-2014) supports the study’s primary argument. The findings presented below show general support for these propositions, making an important contribution regarding applying the displacement theory to different economic contexts, and globally to the study of democratic accountability.